Gender and Generational Differences in Local Knowledge and Preference for Food Trees in Central Uganda and Eastern Kenya - Gachuiri, A.; Paez-Valencia, A.M.; Elias, M.; Carsan, S.; McMullin, S. (Frontiers Media, 2022)
Food trees contribute substantially to the food and nutrition security of millions of rural households in Africa. Farming communities prioritize tree and shrub species on farms based on a combination of factors, including their knowledge of potential uses the species' economic potential and a range of constraints and opportunities that each farmer faces depending on their position within the community and the household, in cultivating, harvesting and processing tree products. Gender and age are strong determinants of such constraints and opportunities as well as ecological knowledge and use of tree resources. This study contributes to the understanding of gender and generational preferences for food tree species that determine their use, and which contribute to food and nutrition security in Central Uganda and Eastern Kenya. Sixteen gender and age segregated focus group discussions were conducted to assess food tree species preferences. A total of 61 food tree species were listed −46 in Uganda (including 16 indigenous species) and 44 in Kenya (21 indigenous species). Results showed knowledge on food tree species differed by gender and age, with differences across gender lines found more prevalently in Uganda, and across generational lines in Kenya. Age-related differences in knowledge and preferences were clear with regard to indigenous species, whereby older women and men were found to have the most knowledge in both countries. Among key challenges for food tree cultivation, farming households mentioned knowledge of tree management, the lack of planting materials, especially for improved varieties, prolonged droughts and scarcity of land. Some of these constraints were gendered and generational, with women mostly mentioning lack of knowledge about planting and management as well as cultural restrictions, such as only having access to land when married; whereas younger men indicated management challenges such as pests, limited markets, as well as scarcity and limited ownership of land. Overall findings suggest that consulting user preferences for food tree species and constraints experienced by gender and age group could be important in the design of interventions which involve a diversity of food trees. Copyright © 2022 Gachuiri, Paez-Valencia, Elias, Carsan and McMullin.